Społeczny aspekt jąkania – wskazówki dla jąkających się i ich rodziców / opiekunów oraz nauczycieli i logopedów - Bijak, Elżbieta (Logopedia Silesiana, 2012)
The social aspect of stammering – practical instructions for stammering people, their parents/legal guardians, teachers and speech therapists The authors who are speech therapists in the field of logopaedics dealing discuss the therapy of people who stammer taking into account the social aspect. They present some practical instructions concerning the process of speech therapy so as to answer the questions asked by people who stammer, their parents/legal quardians, teachers and therapists.